A modulated positioning scheme for asymmetric vibration sensor using high-frequency carrier. (January 2023) - Huang, Yuelang; Liu, Kun; Sun, Zhenshi; Xu, Tianhua; Jiang, Junfeng; Li, Sichen; Jin, Xibo; Xue, Kang; Liu, Tiegen
Abstract : Distributed vibration sensors with standard deviation less than 60 m along the sensing length of 51 km is achieved. The average processing time is 106 ms (less than the sampling time of 0.3 s). Vibrations with weaker energy can be located more accurately, compared with the traditional methods. Abstract: The asymmetric dual Mach-Zehnder interferometer can be used in the vibration sensing system for the long-distance monitoring. It can effectively suppress the backscattering noises of the system. However, it will also seriously deteriorate the positioning accuracy because of the asymmetry of the interferometer. In this paper, a modulated asymmetric dual Mach Zehnder interferometer (ADMZI) system using a high-frequency carrier scheme has been theoretically proposed and experimentally demonstrated. Field trials have been carried out to verify the effectiveness. Our experimental results show that the standard deviation of the proposed scheme is less than 60 m for a sensing length of 51 km, with an average processing time of 106 ms. Compared to traditional methods, the proposed approach can also be applied to weak signals with low frequencies and small amplitudes. This indicates that the proposed scheme can significantly improve the applicability of the asymmetry based distributed sensing systems.